From the editor: halfway through the IPY—halfway for an Antarctic traverse - Goldman, Helle V (Polar Research, 2008)
April is here and we have just passed the midpoint of the International Polar Year (IPY), which began on 1 March 2007 and will conclude on 1 March 2009. The “year” stretches over 24 months to accommodate two summer field seasons in both polar regions. The northern summer is fast approaching, and scientists who will undertake a second IPY summer season in the Arctic are making their final preparations. At the opposite end of the planet, summer is over and scientists have wrapped up the first IPY field season. Those whose projects will carry on for a second summer season will have to wait until late this year to resume work in Antarctica.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Norway and past International Polar Years—a historical account - Bones, Stian (Polar Research, 2007)
Surveying Norway’s role in past International Polar Years (IPYs), this essay by historian Stian Bones contributes to a broader understanding of Norway as a “polar nation”. He describes the strengths of Norway’s scientific traditions in the polar regions, and examines the varying motivations driving Norwegian involvement in the first three IPYs: 1882–83, 1932–33 and 1957–58 (also known as the International Geophysical Year).
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; historie; polarområdene; vitenskap

Fra selfangstskuter til vitenskapelige ekspedisjonsskip. Svend Foyn og ishavsekspansjonen fra Sør-Norge - Christensen, Olav (Norsk sjøfartsmuseum. Årbok, 2007)
Keywords: Carl Anton Larsen; Nordmenn; Sørishavet; Vestfold; ekspedisjoner; fangst; hvalfangere; hvalfangst; oppdagelsesreiser; polarområdene; vitenskap

Polar Research evolves, and Norway and the IPY - Goldman, Helle V (Polar Research, 2007)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap